Constipation and food intake in elderly group: a study bibliographic - Albuquerque, Francisca Rosa Vieira de Sousa (2016)
The following article aims to evaluate the relationship between the elderly, constipation and diet, through integrative and bibliographical research, with descriptive and quantitative approach, performed in the Virtual Library of Health databases and Google Scholar.